(untitled) - Tomlinson, Brian (Cambridge, 2011)
Part A. Data collection and materials development; 2. Using corpora in the language classroom; 3. Concordances in the classroom without a computer:assembling and exploiting concordances of common words; 4. Telling tails: grammar, the spoken language and materialsdevelopment; Part B. The process of materials writing; 5. A framework for materials writing; 6. Writing course materials for the world: a great compromise; 7. How writers write: testimony from authors; Part C. The process of materials evaluation; 8. The analysis of language teaching materials: inside the Trojan Horse; 9. Macro- and micro-evaluations of task-based teaching; 10. What do teachers really want from coursebooks?; 11. The process of evaluation: a publisher's view; Part D. The electronic delivery of materials; 12. Developing language-learning materials with technology; 13. New technologies to support language learning;; Part E. Ideas for materials development; 14. Seeing what they mean: helping L2 readers to visualise; 15. Squaring the circle - reconciling materials as constraint with materials as empowerment; 16. Lozanov and the teaching text; 17. Access-self materials
Keywords: Language and languages -- Study and teaching; Ngôn ngữ -- Học và dạy